Pemberdayaan UMKM Jeger Buana Melalui Pengembangan Produk Kripik Singkong dari Program Magang Industri PT. Vena Energy - Rahmatullah, Fajar Iqbal Fatur; Mu'minin, Amirul; Agung Budi Muljono (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
PT Vena Energy is a company focused on the development of renewable energy, particularly in the field of Solar Power Plants (PLTS), and is part of the Asia-based Vena Energy Group, which is strongly committed to providing clean and sustainable energy solutions. Through its industrial internship program, PT Vena Energy also implements community empowerment initiatives aimed at improving local economic welfare. The Selong Solar Power Plant, located in Geres Village, Labuhan Haji District, East Lombok Regency, West Nusa Tenggara, has become the center of one such initiative, namely the development of a home-based cassava chip processing industry known as “Krupuk Jeger”, which is expected to enhance the economic quality of the local community by increasing the added value of local products. This study applies a qualitative method with data collected through direct interviews with business actors and supported by literature reviews from legislation, books, and relevant journals on SME production and development. The community has demonstrated active participation in both social activities and collaboration with local organizations and government, yet to further strengthen the development of Krupuk Jeger, it remains necessary to provide facilities or platforms that can accommodate workers and encourage their active involvement in business activities.